Complete mitochondrial genome and the phylogenetic position of the Sphaeroma sp. (Crustacea, Isopod, Sphaeromatidae) - Mingliu Yang; Tingwei Gao; Ding Hui; Xiao Chen; Wenai Liu (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitogenome of Sphaeroma sp. (Crustacea, Isopod, Sphaeromatidae) was determined in this study. The total length of mitogenome was 15,839 bp, and contained 13 protein-coding genes, 21 tRNA genes, 2 rRNA genes, 1 control region, and 2 unknown fragments which longer than 200 bp. The nucleotide composition was 25.80% A, 16.56% C, 25.94% G and 31.67% T. Six initiation codons (ATA, ATC, ATG, ATT, ACG, GTG) and three termination codons (TAA, TAG, TA–) were used in the protein-coding genes. The length of tRNA genes ranged from 52 to 65 bp, and tRNA-Arg was not identified. The phylogenetic result showed Sphaeroma sp. was closely related to Sphaeroma terebrans with high bootstrap value supported.